microRNA-126 Is a Tumor Suppressor of Granulosa Cell Tumor Mediated by Its Host Gene EGFL7 - Tu, Jiajie; Cheung, Hoi-Hung; Lu, Gang; Chan, Clement Leung-Kwok; Chen, Zijiang; Chan, Wai-Yee (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) are small noncoding RNAs that play important roles in gene regulation at post-transcriptional level. In the current study, we examined the effect of miR-126 on granulosa cell tumor (GCT), a subtype of ovarian cancer. miR-126 expression was repressed in tissues from malignant GCT patients. We showed that miR-126 could inhibit cell proliferation, migration/invasion, ovarian hormone production and promote anticancer drug-induced apoptosis in vitro. The ‘tumor suppressor’ role of miR-126 was further validated in an mice GCT model in vivo. By RNA-seq, immunohistochemical staining (IHC), Western blot and luciferase reporter assay, we identified and confirmed EGFL7 as a direct functional target of miR-126 in cancer GCs. Furthermore, we found AKT signaling pathway was associated with miR-126 and EGFL7 in cancer GCs. Taken together, our results demonstrate a function of miR-126 in the repression of GCT development via regulating EGFL7.